KONSEP TENTANG NILAI-NILAI ETIKA GURU DALAM KITAB ADABUD DUNYA WA ADDIN KARYA IMAM AL MAWARDI - Dewi Rizqa Tamia; Maryono Maryono; Salis Irvan Fuadi (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to: 1) find out the concept of teacher ethical values ​​in the book Adabud dunya wa addin by Imam Al Mawardi, 2) find out the specificity of teacher ethics in the book Adabud dunya wa addin by Imam Al Mawardi, 3) find out the actualization of teacher ethical values in the adabud dunya wa addin book if it is applied in the present. The background of this research is based on several issues regarding teacher ethical values, in which educators must have good ethical values ​​but there are still many educators/teachers who do not understand that, so it is necessary to carry out a process of implementing these values. good teacher ethics in various ways or methods that have been taught by previous figures or scholars. This study uses a qualitative research approach where the type of research is library research. In collecting data using documentation methods and online data tracking. Then, data sources were obtained from primary data sources and secondary data (adabud dunya wa addin books, references related to teacher ethical values, previous research, articles and internet sites). The analysis technique used is content analysis technique. Where content analysis is observing the content of information in writing. The results of the study show that: 1) The concept of teacher ethical values ​​in the adabud dunya wa addin book is to make an educator/teacher aware of how important it is to have good ethical values ​​in order to be a role model/good example for their students so they can creating a generation of educators with good morals; 2) The specificity of teacher ethics in the book Adabud Dunya Wa Addin is the special ethical values ​​contained in the book Adabud Dunya Wa Addin taught by Imam Al Mawardi as a teacher must have ethics, as follows: tawadhu', practicing his knowledge, being generous for his knowledge, guiding students, ridding themselves of doubtful jobs, aiming to hope for the blessing of Allah, respecting their students, and giving advice and being gentle with their students. That is also the objective of an educator's benchmark, namely to make educators become human beings who have good morals; 3) the actualization of teacher ethical values ​​in the adabud dunya wa addin book when applied today is also an illustration that in fact there is still a teacher who applies these teacher ethical values ​​properly in an institution, forum, or between individuals. This is a race that anyone can and can apply these ethics properly.